PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI MALUKU - Senda Yunita Leatemia (Jurnal Cita Ekonomika, 2017)
The research carried out to know the influence of local tax and retribution on the improvement of local government original receipt (Pendapatan Asli Daerah/PAD). The population of research are whole of regency/municipality in Provinsi Maluku, by eleven samples of regency/municipality. The research’s data taken from the actual of local government budget (Anggaran Pendapatan Belanja Daerah/APBD) that taken from five years, starting from 2011 until 2015. Data achieved from Badan Pusat Statistik (BPS) Republik Indonesia with total samples are fifty-five. Regression shown that there are the influence among local tax and retribution on local government original receipt. This case shown that local tax and retribution give high contribution to improve the local government original receipt.